Dividend Pay-out Policy and Share Price: A Study of Listed Firms in Morocco - Lamyaa, Riad; Meriam, Dekri; Karima, Touili (European Scientific Journal, ESJ, 2022)
The main purpose of this study is to examine the relationship between dividend policy and financial performance in Morocco stock market. The panel data regression method is used to analyze the relationship of share price with dividend per share. This study presumes that dividend policy has an effect on the share price in Morocco. Also, it assumes that companies that pay dividends tend to have a higher financial performance than those that do not. On the other hand, companies that do not distribute dividends are more indebted and have a smaller size compared to distributors. The results of the econometric analysis conducted indicate that the dividends distributed and the profits are found to be significantly positive for the financial performance of Moroccan companies.